The Implementation of the Student Team Achievement Division (STAD) Learning Strategy Assisted by Wordwall in Improving Students' Understanding of Akidah Akhlak Subjects at MTs Hidayatul Muhajirin Palangka Raya - Wirayudha, Ramadhan; Mazrur, Mazrur; Azis, Abdul; Jasiah, Jasiah (-, 2025)
This research is motivated by the moral crisis and the lack of students' understanding in the subject of Akidah Akhlak at MTs Hidayatul Muhajirin Palangka Raya, where the learning process is still dominated by expository teaching strategies (lectures or verbal explanations). Therefore, this study aims to improve students' understanding of the Akidah Akhlak subject through the implementation of the Student Team Achievement Division (STAD) learning strategy assisted by wordwall. The research uses a quantitative method with a quasi-experimental type in the form of a nonequivalent control group design. Data were collected through observation and tests (pretest and posttest) in the experimental class (STAD assisted by wordwall) and the control class (expository). Observation results showed that the implementation of the STAD strategy assisted by wordwall was carried out very well (reaching 95.8%). The independent sample t-test analysis showed a significance value of 0.000, which means there is a significant difference in students' understanding, where the average posttest score of the experimental group (88.93) is much higher than the control group (80.48). Furthermore, the N-Gain test produced a score of 0.6027 (medium category). It can be concluded that the implementation of the STAD learning strategy assisted by wordwall is effective in improving students' understanding in Akidah Akhlak subjects.